The Delphi technique in identifying learning objectives for the development of science, technology and society modules for Palestinian ninth grade science curriculum - Daniel, E.G.S.; Abualrob, M.M.A. (Routledge, 2011)
This article outlines how learning objectives based upon science, technology and society (STS) elements for Palestinian ninth grade science textbooks were identified, which was part of a bigger study to establish an STS foundation in the ninth grade science curriculum in Palestine. First, an initial list of STS elements was determined. Second, using this list, ninth grade science textbooks and curriculum document contents were analyzed. Third, based on this content analysis, a possible list of 71 learning objectives for the integration of STS elements was prepared. This list of learning objectives was refined by using a two-round Delphi technique. The Delphi study was used to rate and to determine the consensus regarding which items (i.e. learning objectives for STS in the ninth grade science textbooks in Palestine) are to be accepted for inclusion. The results revealed that of the initial 71 objectives in round one, 59 objectives within round two had a mean score of 5.683 or higher, which indicated that the learning objectives could be included in the development of STS modules for ninth grade science in Palestine.